Model-Based Learning Approach: Effects on Students’ Academic Performance and Attitudes in Earth science - Canlas, Annalyn Cayago; Guevarra, Maydeen Dizon (FKIP Universitas Lampung, 2020)
This study determined the effect of the model-based learning approach on students’ academic performance and attitudes in Earth science as well as the teachers perception. A total of four science teachers served as teacher-respondents and sixty-one of ninth-grade students served as student-participants in the research. To answer the objectives of the study, the science attitudes scale, standardized test, and perception survey questionnaire were administered. T-test was utilized to determine the significant difference in the students’ academic performance and attitudes in learning earth science and SWOT analysis was utilized on teachers’ perception. Findings revealed that the model-based learning and conventional approaches are both effective in enhancing students’ academic performance in earth science which the first approach has a positive effect on the student’s attitude toward science. Moreover, SWOT analysis revealed that the model-based learning approach is a learner-centered and teacher-facilitated approach that adheres to the goal and principles of K to 12 Basic Education Program of enhancing learners interest and motivation, maximizing learners’ 21st-century skills and scientific skills leading into holistically skill-competent learners through the model building. The overall result indicates that the model-based learning approach is a promising teaching strategy that can help improve students’ academic performance and develop a positive mindset in learning science. Keywords: model-based approach, attitudes toward earth science, academic performance. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp49-66